12. RESULTS AND NEEDS OF INTERVENTIONAL GASTROINTESTINAL ENDOSCOPY ON PATIENTS WITH GASTROINTESTINAL DISEASES WHO UNDERWENT DIAGNOSTIC GASTROINTESTINAL ENDOSCOPY AT SONG LO DISTRICT MEDICAL CENTER, VINH PHUC PROVINCE IN 2020-2022 (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to describe the diagnostic endoscopy results and the demand for interventional gastrointestinal endoscopy among patients with gastrointestinal diseases at Song Lo district Medical Center, Vinh Phuc province, period 2020-2022.Methods: A cross-sectional study was conducted on 384 patients with gastrointestinal diseases who underwent diagnostic endoscopy at Song Lo district Medical Center. Data were collected through structured questionnaire-based interviews. The data were entered into Epiinfo and analyzed using SPSS 20.0.Results: The diagnostic gastrointestinal endoscopy technique at Song Lo district Medical Center during 2020-2022 achieved a high success rate; a total of 80.7% of patients were satisfied with the treatment process, and 80.7% expressed a demand for returning to the center for interventional gastrointestinal endoscopy.Conclusion: The study results highlight the necessity of implementing interventional gastrointestinal endoscopy at Song Lo district Medical Center to meet patient demands and reduce the burden on higher-level hospitals.
Keywords: Gastrointestinal diagnosis; endoscopy; intervention needs; results; Song Lo district Health Center